EFFECTIVE COMMUNICATION IN NURSING: A COMPREHENSIVE SYSTEMATIC REVIEW OF BEST PRACTICES - Citra Suraya, Citra Suraya; Tukimin bin Sansuwito; Regidor III Dioso; Aris Citra Wisuda (Citra Internasional Institute, 2024)
Background: Effective communication is crucial in patient safety management, as it minimizes and prevents actions that could negatively impact nursing care. Effective communication involves strategies to ensure clear and accurate message delivery, enhance patient safety, and reduce work-related risks for nurses and other healthcare professionals. This can be initiated by adhering to Standard Operating Procedures for effective communication and leveraging virtual technology. Objectif: This research aims to identify the implementation of effective communication in the context of patient safety within nursing care settings. Method: The article search involved querying five databases: PubMed, ProQuest, ScienceDirect, DOAJ, and Garuda. The analysis method included selecting journals relevant to the research purpose and thoroughly reading each. Inclusion criteria for this literature review encompassed communication, nurses, nursing service settings, and journal articles published within the last five years. Exclusion criteria included journals that were not open access, articles with unclear or unstructured research methods, articles available only in abstract form, systematic reviews, and scoping reviews. Results: Through feasibility testing, eight journal articles were identified that demonstrated the application of effective communication in the context of patient safety. These included communication training programs, interprofessional team integration in service, and communication management focused on patient safety. Effective communication can be achieved successfully when nurses are adept at selecting appropriate communication methods tailored to the specific needs of the nursing service setting.